PENGGUNAAN MEDIA BUKU DAN VIDEO PEMBELAJARAN DALAM KONTEKS PENINGKATAN EFEKTIVITAS PEMBELAJARAN DI PERPUSTAKAAN SEKOLAH - Maulinda, Nosa; Mustajib (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
SMPN 2 Kepung Library is a technical implementation unit that provides school equipment in the fields of education, teaching, and research. The library is managed by Karpiati, S.Pd., M.Si. in this article the type of research is descriptive qualitative which aims to explore the role of libraries as learning media in SMPN 2 Kepung. The research method uses descriptive qualitative conducted through observation, interviews, and document analysis to understand the role of libraries in supporting the learning process in schools. The purpose of the study is to evaluate the effectiveness of libraries as a learning medium in increasing student learning motivation, expanding their knowledge, and providing useful learning experiences. Regarding the results of the study, research shows that the library at SMPN 2 Kepung has a significant role as an effective learning medium. The use of libraries as learning resources has made a positive contribution in improving the quality of education, motivating students to learn through literacy programs, and providing valuable learning experiences. Therefore, the role of libraries as learning media needs to be strengthened and managed properly to support an effective and efficient education process in schools by developing these literacy programs.